Effect of food insecurity on hazardous alcohol consumption and psychological well-being among people with tuberculosis in Kampala, Uganda - Jonathan Izudi; Saidi Appeli; Francis Bajunirwe (Elsevier Ltd, 2025)
Rationale: Food insecurity (FI), hazardous alcohol consumption (HAC), and poor mental health are common among people with tuberculosis (TB), yet empirical evidence on their interrelationships remains limited. Objective: We evaluated the effect of FI on HAC and psychological well-being among people with pulmonary TB in Kampala, Uganda. Methods: We collected data across five TB clinics and constructed a quasi-experimental design. FI was the exposure, measured using the FI Experience Scale (FIES). FIES scores range between 0 and 8, and individuals were classified as food insecure if they scored ≥ 4. The primary outcome was HAC, assessed using the Alcohol Use Disorders Identification Test (AUDIT) tool. Participants with AUDIT scores ≥ 16, indicating high-risk drinking or possible alcohol dependence, were categorized as having HAC. The secondary outcome was psychological well-being measured using the World Health Organization’s Five Well-Being Index, with a total score of <15 indicating poor psychological well-being. We used doubly robust estimation to report causal risk ratios (RR) and 95 % confidence intervals (CI). Results: Of 818 participants, 475 (58.1 %) were from food-insecure households, 153 (18.7 %) had HAC, and 316 (38.6 %) had poor psychological well-being. FI was independently associated with HAC (RR 1.43, 95 % CI: 1.21–1.69), but not poor psychological well-being (RR 1.06, 95 % CI: 0.81–1.37). Conclusion: FI is associated with a higher likelihood of HAC but not psychological well-being among people with TB in Kampala, Uganda. Given their high prevalence, there is a need to address food insecurity, HAC, and poor psychological well-being within TB control programs.
Keywords: Alcohol consumption; Food insecurity; Psychological well-being; Tuberculosis; Uganda